Management of behavioral consequences in education - Michael, Jack (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This paper represents a first attempt at an analysis of the educational process in terms of principles of behavior derived from the laboratory. One of the most rapidly developing areas within modern experimental and applied psychology is the science and technology of behavior consequences, and before undertaking a more detailed analysis of the instructional process, it seems appropriate to introduce some of the terminology and principles of the science. This is, in fact, what is done in Part A of this discussion. Part B, due to appear in the coming issue of this Journal (Volume III, No. 4), will deal with the above mentioned detailed analysis and will consider possibilities for improving educational practice.